Deriving OCL Optimization Patterns from Benchmarks - Sánchez Cuadrado, Jesús; Jouault, Frédéric; García-Molina, Jesús; Bézivin, Jean (Electronic Communications of the EASST, 2008)
Writing queries and navigation expressions in OCL is an important part of the task of developing a model transformation definition. When such queries are complex and the size of the models is significant, performance issues cannot be neglected.In this paper we present five patterns intended to optimize the performance of model transformations when OCL queries are involved. For each pattern we will give an example as well as several implementation alternatives. Experimental data gathered by running benchmarks is also shown to compare the alternatives. The model transformation benchmark framework developed to obtain these results is also described.